2014
DOI: 10.1007/s00436-014-4170-8
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody against recombinant Fasciola gigantica cathepsin L1H could detect juvenile and adult cathepsin Ls of Fasciola gigantica

Abstract: Cathepsin Ls (CatLs), the major cysteine protease secreted by Fasciola spp., are important for parasite digestion and tissue invasion. Fasciola gigantica cathepsin L1H (FgCatL1H) is the isotype expressed in the early stages for migration and invasion. In the present study, a monoclonal antibody (MoAb) against recombinant F. gigantica cathepsin L1H (rFgCatL1H) was produced by hybridoma technique using spleen cells from BALB/c mice immunized with recombinant proFgCatL1H (rproFgCatL1H). This MoAb is an immunoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…gigantica ; however, the MoAb showed strong cross-reactions with other parasite antigens. In addition, Wongwairot et al [ 33 ] revealed that MoAb could detect isoforms of cathepsin Ls of both juvenile and adult F . gigantica .…”
Section: Discussionmentioning
confidence: 99%
“…gigantica ; however, the MoAb showed strong cross-reactions with other parasite antigens. In addition, Wongwairot et al [ 33 ] revealed that MoAb could detect isoforms of cathepsin Ls of both juvenile and adult F . gigantica .…”
Section: Discussionmentioning
confidence: 99%
“…It was found that cross-reactivity with S. mansoni antigen occurred by using these MoAbs. Another study of F. gigantica revealed that MoAb against isoforms of cathepsin Ls of juvenile and adult fluke was used for diagnosis of animal fasciolosis (Wongwairot et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The cross-reactivities among antibodies to cathepsin L isotypes were due to the similarity and identity of their amino acid sequences. Localization of FgCatL1H by both polyclonal and monoclonal antibody showed its expression in the epithelial cells of intestinal tract of metacercariae, NEJ, 2-and 4-week-old juveniles, and adult F. gigantica Wongwairot et al 2015). The positive result in the adult might be due to a high degree of cross-reaction between FgCatL1H, which is the juvenile isoform, with the adult-specific cathepsin L. By contrast, FhCL3 was also detected by using its corresponding antibody in oral and ventral suckers and tegument of F. hepatica NEJ (Zawistowska-Deniziak et al 2013).…”
Section: Cathepsin Lmentioning
confidence: 97%